Cloning of a HcCreb gene and analysis of its effects on nacre color and melanin synthesis in Hyriopsis cumingii. - Mengying Zhang (Public Library of Science (PLoS), 2021)
Creb (Cyclic AMP response element binding protein) is a nuclear regulatory factor that regulates transcription through autophosphorylation. In melanocytes, cAMP's corresponding elements bind to the Creb protein to autophosphorylation and activate MITF (Microphthalmia-associated transcription factor). MITF stimulates Tyrosine(tyr) to induce melanocytes to differentiate into eumelanin and pheomelanin. In this study, a HcCreb gene in Hyriopsis cumingii was cloned and its effects on melanin synthesis and nacre color were studied. HcCreb was expressed in both purple and white mussels, and there was a significant difference in expression between adductor muscle (p<0.01) and mantle tissue (p<0.05). Other tissues did not show significant differences (except for gill tissue), and in general, the level of mRNA expression was higher in purple mussels than in white mussels. In both white and purple mussels expression levels in gill tissue was the highest, followed by the mantle. Strong and specific mRNA signals were detected in the dorsal epithelial cells of the mantle pallial layer, indicating that HcCreb may be involved in nacre formation. After arbutin treatment, the expression of HcCreb decreased significantly. By further testing the changes in mantle melanin content it was found that the melanin content after arbutin treatment decreased significantly compared to the control group (p<0.05). It is speculated that the HcCreb gene plays a role in the process of melanin synthesis and nacre color formation in H. cumingii.